An Exploration of Recent Developments in Public Policy Management: A Bibliometric Study - Gunawan Undang (Kontigensi : Jurnal Ilmiah Manajemen, 2024)
Public policy management is a vital area in government decision making that affects society at large. In an effort to understand the latest developments in this domain, bibliometric studies are a relevant and effective approach. This article aims to explore current research trends in public policy management through bibliometric analysis of documents indexed in the Scopus database. Through careful searching and application of strict inclusion criteria, we identified 111 documents relevant to this topic. Our analysis includes mapping collaboration networks between researchers, identifying the most frequently cited publications, as well as analyzing the keywords that most commonly appear in the literature. The results provide in-depth insight into recent research trends, dominant research focuses, and contributions of leading researchers in the field of public policy management. It is hoped that this article will be a valuable reference source for researchers, practitioners and decision makers who are interested in understanding and developing effective and sustainable public policies.